Design and Implementation of a Smart Industrial Gateway for CNC Machines Using ESP32-WROOM-32 - Ashwini M S; Dr Punith Kumar M B; Thejesh P (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The advancement of Industry 4.0 has revolutionized manufacturing systems by introducing intelligent, interconnected environments aimed at enhancing operational efficiency, minimizing downtime, and enabling data-driven decision-making. This paper presents the design and implementation of a Smart Industrial Gateway developed using the ESP32-WROOM-32 microcontroller. The system is designed to monitor and log key operational signals from CNC machines, specifically machine status, cycle status, alarm signals, and emergency triggers. Real-time signal acquisition is achieved through hardware interrupts, with concurrent processing managed by the FreeRTOS operating system. The collected data is stored locally in a binary format, with each entry timestamped using NTP synchronization. A multi-layered communication system ensures reliable internet connectivity, prioritizing GSM, Ethernet, and Wi-Fi, and enabling secure data transmission to a central cloud server using HTTP. The system also integrates Modbus RTU communication over RS485 for reading energy consumption data from industrial meters. Upon internet availability, the system automatically uploads the stored data and deletes it from the local memory, optimizing storage. The proposed solution enhances visibility into machine status and energy usage, facilitating timely diagnostics and supporting energy-efficient operations. This work lays the foundation for implementing predictive maintenance strategies and remote diagnostics in traditional manufacturing setups, contributing to the broader adoption of Industrial Internet of Things (IIoT) technologies.
Keywords: Industry 4.0; Smart Industrial Gateway; ESP32-WROOM-32; CNC Machines; FreeRTOS; Modbus RTU; IoT; Real-Time Monitoring; Cloud Communication; Energy Consumption; Predictive Maintenance; HTTP Transmission; Embedded Systems